Approaching the social recruiting of teachers from a comparative analysis in three jurisdictions: Buenos Aires City, La Pampa and Santa Cruz (Praxis Educativa, 2012)
In Argentina, teachers have traditionally been characterized as part of the middle class or the petty bourgeoisie, depending on the theoretical perspective. This characterization is usually based on the predominantly female composition of teachers as a group and on their character of wives of that portion of the population that occupies “relatively important positions in the social structure”. However, few studies have attempted to account for this hypothesis and most of them are based on unrepresentative samples. In this paper we present an exercise based on a comparison of census data for three jurisdictions which have different features both in the recruitment of teachers and in their specific social and economic structures: Ciudad de Buenos Aires, La Pampa and Santa Cruz.
Keywords: teachers; middle classes; social position; social structure; social recruitment